Caffeine, maximal power output and fatigue. Issue 4 (December 1988) - Williams, J H; Signorile, J F; Barnes, W S; Henrich, T W
Abstract : The purpose of this investigation was to determine the effects of caffeine ingestion on maximal power output and fatigue during short term, high intensity exercise. Nine adult males performed 15 s maximal exercise bouts 60 min after ingestion of caffeine (7 mg.kg-1) or placebo. Exercise bouts were carried out on a modified cycle ergometer which allowed power output to be computed for each one-half pedal stroke via microcomputer. Peak power output under caffeine conditions was not significantly different from that obtained following placebo ingestion. Similarly, time to peak power, total work, power fatigue index and power fatigue rate did not differ significantly between caffeine and placebo conditions. These results suggest that caffeine ingestion does not increase one's maximal ability to generate power. Further, caffeine does not alter the rate or magnitude of fatigue during high intensity, dynamic exercise.